Feminisme Dalam Pemberitaan Media Online Konde.co (Studi: Analisis Wacana Kritis) - Afifah, Nisa; Rifa'i, Akhmad (Ar-Raniry State Islamic University, Indonesia, 2024)
The mass media and online portray women unequally in their current coverage, with efforts to normalize discrimination against women. This paper aims to describe feminism toward Critical Discourse Analysis (AWK) in Konde.co online media. The method used in this paper is the descriptive-qualitative method, which involves obtaining data through observation and documentation. The results of this paper show that the news on Konde.co's online media contains feminist discourse. Konde.co takes sides with women in accordance with the ideology of the media, which refers to the feminist movement. Reporting on Konde.co's online media always raises issues related to defending women in writing its news. Konde.co, which has a direct alliance with women, also provides advocacy for women who are oppressed and subordinated by society. Even though the position of women is placed as an object, the Konde.co media still prioritizes it and does not corner it in the news text. Therefore, konde.co, which has feminist characteristics as a differentiator from other media, must be able to maintain the existence and consistency of its media ideology in order to provide a balanced education to the public.